Lipophilic bioactive compounds from thermophilic cyanobacterium Leptolyngbya sp. HNBGU-004: Implications for countering VRSA resistance - Sachin Tyagi; Rahul Kunwar Singh; Ashok Kumar (Heliyon, 2024)
Extremophiles thrive in extreme conditions, showcasing rich and unexplored diversity. This resilience hints at the existence of novel biochemical pathways and unique bioactive compounds. In contrast, the issue of drug resistance and excessive misuse of antibiotics in various settings, such as healthcare, agriculture, and veterinary medicine, has contributed to the emergence and spread of drug-resistant microorganisms.In the present research, Leptolyngbya sp. HNBGU-004, was obtained from an extreme location, a hot water spring in the Garhwal Himalayan region of India. The lipophilic fraction derived from Leptolyngbya sp. HNBGU-004 exhibited significant inhibitory effects against vancomycin-resistant Staphylococcus aureus (VRSA), displaying a bactericidal concentration of 0.5 mg mL−1. Furthermore, gas chromatography-mass spectrometry (GC-MS) analysis of the lipophilic extract unveiled the major constituents.Leptolyngbya sp. HNBGU-004 holds significant promise as a primary source of potent anti-vancomycin-resistant S. aureus components. These findings emphasize the importance of Leptolyngbya sp. HNBGU-004 as a foundational source for use as both a synergistic and alternative agent against VRSA.